Returning to work after stroke: perspectives of employer stakeholders, a qualitative study. - Coole, Carol; Radford, Kathryn; Grant, Mary; Terry, Jane (Springer, 2012)
Purpose: More than 40 % of working age adults with stroke fail to return to work. The work context is a key factor in return to work, but little is known about the experiences of employers in supporting employees with stroke. The aim of this study was to explore return to work after stroke from the employer perspective, to identify key features associated with success and to seek participants’ views regarding the role of healthcare in return to work. Methods: Data was gathered through 18 semi-structured interviews with employer stakeholders and included small business owners, line managers, human resources and occupational health staff. Data was analysed thematically. Results: The main themes identified were: the impact of stroke on the employer, characteristics of the employee, communication, knowledge and information, experience of other stakeholders, integrating healthcare in return to work. Conclusion: Employers face complex emotional and practical issues when helping an employee return to work after stroke, for which many lack knowledge and experience. The range and quality of support networks that they access is variable and advice and support from clinicians is welcomed. Further research is necessary to investigate how such support could be funded and integrated within existing service provision.